2000
DOI: 10.1007/s004220000190
|View full text |Cite
|
Sign up to set email alerts
|

Muscle contraction history: modified Hill versus an exponential decay model

Abstract: In recent years, it has been recognised that improvements to classic models of muscle mechanical behaviour are often necessary for properly modelling coordinated multi-joint actions. In this respect, the purpose of the present study was to improve on modelling stretch-induced force enhancement and shortening-induced force depression of muscle contraction. For this purpose, two models were used: a modified Hill model and a model based loosely on mechano-chemistry of the cross-bridge cycle (exponential decay mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…In analogy to Wilson et al (2001) and Siebert et al (2003), we observed oscillations of the loading mass when trying to simulate concentric muscle contraction experiments with an established Hill-type muscle model (Zajac 1989;van Leeuwen 1992;van Soest and Bobbert 1993;Meijer et al 1998;Ettema and Meijer 2000;Günther and Ruder 2003). It is also known that Hill-type muscle models fail to describe energy absorption of high-frequency oscillations at low amplitudes.…”
mentioning
confidence: 57%
“…In analogy to Wilson et al (2001) and Siebert et al (2003), we observed oscillations of the loading mass when trying to simulate concentric muscle contraction experiments with an established Hill-type muscle model (Zajac 1989;van Leeuwen 1992;van Soest and Bobbert 1993;Meijer et al 1998;Ettema and Meijer 2000;Günther and Ruder 2003). It is also known that Hill-type muscle models fail to describe energy absorption of high-frequency oscillations at low amplitudes.…”
mentioning
confidence: 57%
“…Force depression has often been associated with the speed of shortening: increasing when the speed of shortening was decreasing (De Ruiter et al 1998;Ettema and Meijer 2000;Josephson and Stokes 1999;Marechal and Plaghki 1979). However, Leonard and Herzog (2005) performed a series of experiments on cat soleus where they demonstrated that force depression at diVerent speeds of shortening (but the same force during shortening) was constant whereas force depression increased for increasing force during shortening (but at the same speed of shortening).…”
Section: Residual Force Depressionmentioning
confidence: 91%
“…First, however, we briefly refer to the history of the theory of muscle activation, which dates back to the work of Hill (1938). Based on the threeelement Hill model several models have been developed; here, however, we mention in particular the papers by Ettema & Meijer (2000), Lloyd & Besier (2003) and Lichtwark & Wilson (2005), which collectively provide an overview of the literature although they do not particularly focus on the contraction of smooth muscle cells. Papers which capture smooth muscle contractions and related models, also based on the Hill model, are those by Gestrelius & Borgström (1986), Yang et al (2003a) and Zulliger et al (2004b), which are now summarized briefly.…”
Section: Active Response Of Artery Wallsmentioning
confidence: 99%